Digital Technologies in Public Administration Networks: Systematic Literature Review and Research Avenues. - Sienkiewicz-Małyjurek, Katarzyna; Zyzak, Barbara (Administration & Society, 2025)
This article reviews three decades of scholarly discourse to deepen our understanding of the role of digital technologies in public administration networks. Using PRISMA methodology, a systematic review of 59 publications retrieved from the Web of Science and Scopus databases was conducted to unpack and systematize existing knowledge on the foundations and evolution of digital technologies, assess their scope of application, and identify key factors influencing their use within public administration networks. Findings indicate a fragmented and uneven research landscape, with digital technologies primarily leveraged in governance and collaborative networks, rather than in policy networks. While ICT continues to serve as a foundational technology across all three domains, a notable shift is occurring: modern technologies, such as AI, blockchain, big data, and social media are gaining traction across public services, particularly in emergency response, public safety, healthcare, and education. This study provides a comprehensive overview, highlights research gaps, and suggests future research directions.